Selective oxidization of 2- and 3-aminotoluene by ozone in the glacial acetic acid to the corresponding aminobenzoic acids - Bushuyev, Andrey (Eastern-European Journal of Enterprise Technologies, 2014)
The kinetic regularities and mechanisms of oxidation reactions of 2- and 3-aminotoluene and its acylation derivatives by the gases that contain ozone in the glacial acetic acid have been studied. It has been established that ozone attacks mainly the lone pair of electrons of the nitrogen atom with formation, mainly, of polymers of azo compounds. The products oxidation on methyl group are not formed in these conditions. The direction of the ozone’s attack can be altered and directed on the methyl group, as well as by an aromatic ring, by acylation of the amino group. The total yield of the products of oxidation of the methyl group of 2- and 3-acetamidotoluene is 5,1 and 12,4 % respectively. The process of liquid-phase catalytic oxidation of 2- and 3-acetamidotoluene by the ozone in the presence of transition metal salts and their mixtures with potassium bromide to the corresponding acetamidobenzoic acids has been investigated as well. At the presence of acetate Co (II) the output of 2- and 3-acetamidobenzoic acid 25,0 and 31,2% respectively. We found out that the use of our catalytic system (ozone – acetamidotoluene - Co (III) – glacial acetic acid - potassium bromide) significantly increases the reaction rate and the selectivity of substrate oxidation of methyl groups. The main product of oxidation of 2- and 3-acetamidotoluene becomes 2- and 3-acetamidobenzoic acid (55,0 and 71,2 % respectively). Replacing ozone-air mixture with the ozone-oxygen mixture leads to higher yield of 2-acetamidobenzoic acid 70,0 % and 3- acetamidobenzoic acid 86,0 %.